Role of HR and in Bridging the ‘Skill Gap’ in Technology Start Ups - S Kazi, Nikhat; Afzalur Rahman, Dr. (International Journal of Engineering and Technology, 2018)
You donâ€™t Build Business , You Build PeopleÂ ,and the People Build the Business-Zig ZiglarÂ Â